Solubilización de fuentes de fósforo asociadas a un compuesto orgánico enriquecido con biofertilizantes - Rosatto-Moda, Leandro [UNESP]; Mello-Prado, Renato de [UNESP]; Castellanos-Gonzáles, Leónides; Reyes-Hernández, Alfredo; Caione, Gustavo [UNESP]; Silva-Campos, Cid Naudi [UNESP] (Colegio De Postgraduados, 2014)
The enrichment of an organic compound with biofertilizers of microorganisms (solubilizing phosphorus bacteria, BSF) can improve the properties of phosphate fertilizers applied to soils to increase nutrient availability. The experimental design was randomized complete blocks with a factorial 4x2 +1 arrangement of treatments: 1) four sources of phosphorus: phosphate rock, natural phosphate, triple superphosphate (TSP) and Cuban phosphate rock; 2) two sources of bio-fertilizer prepared from filter cake (cane waste) enriched with microorganisms and no enrichment; 3) and an absolute control (no filter cake or fertilizer); repeated three times. Data was analyzed with ANOVA and treatment means were compared using Tukey (p <= 0.05). Assessments of available P (Bray-2 and Oniani methodology) and the quantification of total and solubilizing bacteria and fungi in the soil were performed 30, 60 and 90 d after starting the experiment. After 60 d, the population of BSF was lower in the control (p <= 0.05) and the content of P (Bray-2) was higher for SFT (p <= 0.01). The application of the bio-fertilizer increased the P content compared to the control. At 90 d P (Bray-2) increased with the SFT treatment, which also increased (p P in the soil at 60 and 90 d regardless of the presence of microorganism-enriched bio-fertilizer. The use of filter cake enriched with microorganisms associated with different sources of P, and applied to the soil with a high content of P, did not change the soil populations of total and solubilizing bacteria and fungi in the short term. TSP promoted the highest levels of P in the soil, irrespective of the presence of the organic compound enriched with P solubilizing microorganisms.

El enriquecimiento de un compuesto orgánico con biofertilizantes a base de microorganismos (bacterias solubilizadoras de fósforo, BSF) puede mejorar las propiedades de los fertilizantes de fosfato aplicados a los suelos para mayor disponibilidad de nutrimentos. El diseño experimental fue bloques completos al azar en un arreglo factorial de tratamientos 4x2+1: 1) cuatro fuentes de fósforo: roca fosfatada, fosfato natural, superfosfato triple (SFT) y roca fosfórica cubana; 2) dos fuentes de biofertilizante preparadas a base de cachaza enri-quecida con microorganismos y sin enriquecimiento; y 3) un testigo absoluto (sin cachaza ni abonado); repetido tres veces. Los datos se analizaron con ANDEVA y las medias de tratamientos se compararon con la prueba de Tukey (p£0.05). Las evaluaciones de P disponible (metodología Bray-2 y Oniani) y las cuantificaciones de las bacterias totales y solubilizadoras y de hongos en el suelo se realizaron 30, 60 y 90 d después de iniciar el experimento. Después de 60 d, la población de BSF fue menor en el testigo (p£0.05) y el contenido de P (Bray-2) fue mayor para SFT (p£0.01). La aplicación del biofertilizante aumentó el contenido de P comparado con el testigo. A los 90 d el P (Bray-2) aumentó con el tratamiento SFT, el cual aumentó (p£0.01) el P en el suelo a los 60 y 90 d independientemente de la presencia del biofertilizante enriquecido con microorganismos. El uso de cachaza enriquecida con microorganismos asociada con diferentes fuentes de P, y aplicadas al suelo con alto contenido de P, no alteró las poblaciones de bacterias totales y solubilizadoras y hongos del suelo a corto plazo. El SFT promovió los mayores niveles de P en el suelo, independientemente de la presencia del compuesto orgánico enriquecido con microorganismos solubilizadores de P.
Solubilization of phosphorus sources associated with an organic compound enriched with biofertilizer
Keywords: Available P; Microorganisms; Triple superphosphate; Natural phosphate; P disponible; Microorganismos; Superfosfato triple; Fosfato natural